Integration of differential interferometric synthetic aperture radar and persistent scatterer interferometric approaches to assess deformation in enshi city, hubei, China - Khan, Rehan; Zhong, Yanmei; Li, Huan; Al-Masnay, Yousef A.; Haq, Ihtisham ul; Khan, Musa; Faheem, Haris; Ali, Rashid (Frontiers in Earth Science, 2023)
Land surface deformation is severely damaging the socio-economic conditions of residents globally. It was an aimed to identify Shaziba landslide and further extend our study to assess the deformation activities in Enshi city. For this purpose, the sentinel-1 C-bands data acquired in ascending direction were processed with Sentinel Application Platform (SNAP), Stanford Method for Persistent Scatterers (StaMPS) software packages. Our results revealed the location of landslide that occurred 21 July 2020 at Shaziba area, Enshi prefecture. More interesting deformation results were found in the Enshi city for the first time with deformation range from -51.6 to 54.4 mm/year. Thorough observation of different urban infrastructures such as commercial and residential building, roads, bridges, and airport etc. at Enshi city and along Qingjiang River were considered to evaluate the land surface deformation. Observation revealed that there are number of influencing factors contributing to disturb the natural environment and resources of Enshi prefecture. In these influencing factors major cause is intensive rainfall, infiltration of rainfall into the subsurface Silurian strata together with the load of infrastructures are affecting the study area. This can lead to devastating geo-hazard disaster in the future if more attention has not paid to it. In fact, scientific approaches to determine various causes of frequent geo-hazards in this region is of great significance in early warning system for disaster, and for the safety of residents' lives and property.